Techno-economic analysis and policy implications for promoting residential rooftop solar photovoltaics in Abu Dhabi, UAE. (April 2021) - Alhammami, Hasan; An, Heungjo
Abstract: Although centralized solar systems have developed rapidly, decentralized solar systems are still unattractive to householders in Abu Dhabi due to technical and economic circumstances. This paper addresses this issue through a real-world case study examining the energy potential and economic performance of a rooftop solar system in two residential areas of Abu Dhabi. Then, following an analysis of the energy subsidy structure of Abu Dhabi, a new policy idea is discussed to mitigate the barriers to rooftop solar propagation. For a typical residence, a rooftop photovoltaic system would cover 11–20% of the annual electricity demand, indicating that the current net metering policy would be unattractive or useless to residents. The levelized cost of electricity of the considered system is around 0.05 USD per kWh, which is economically infeasible at the subsidized tariff for UAE nationals. However, at the higher tariff for expatriate residents, its internal rate of return ranges from 9.2 to 12.0%, implying a good possibility of success. This study proposes a new policy for government-led promotion of distributed solar systems through the redistribution of a portion of energy subsidies. This policy would expedite the proliferation of rooftop solar energy and reduce the expenditure for the government subsidy. Highlights: We examine the energy potential of a decentralized rooftop solar system in Abu Dhabi. An economic analysis is performed for a rooftop system on a selected residence. The energy subsidy structure of Abu Dhabi is analyzed to discuss a new policy idea. We propose government-led promotion of distributed solar systems.